A DSP Based Solution to the Early Identification of Hearing Impairment - Valentus, Vincent Peter C.
This paper describes the development of a low cost DSP equation for the early identification of hearing impairment. The desire is to develop a cost-effective, highly sensitive, and easily administered screening system for the evaluation of human hearing acuity.
Keywords: Digital signal processing (DSP); Ear test